Electronic olfactory prototype of an automated malaise detection system for the agricultural industry - Abdul Hamid, Adom, Prof. Madya; Ali Yeon, Md. Shakaff, Prof. Dr.; Mohd Noor, Ahmad, Prof. Dr.; Abu Hassan, Abdullah; Shah Fenner Khan, Mohamad Khan; R. Badlishah, Ahmad, Dr.; Marni Aniza, Markom (Prince of Songkla University, 2011)
Link to publisher's homepage at http://www3.eng.psu.ac.th